Creation of body color mutants by CRISPR/Cas9 gene editing in largemouth bass, Micropterus salmoides - Lina Sun; Tian Gao; Zhiqiang Li; Xiaolong Yang; Zuliang Qin; Mingxiao Ye; Ying Li; Feilong Wang; Deshou Wang (Aquaculture Reports)
Largemouth bass (LMB, Microterus salmoides) is an important commercial freshwater fish, and body color is a key economic trait for quality improvement. Gene editing has not been established in LMB due to the unavailability of one-cell fertilized eggs. In this study, three types of pigment cells, melanophores, iridophores and xanthophores were identified in LMB and melanophores were found first appeared in the iris of eyes in larvae 1.5 days after hatching. The fertilized eggs were obtained through hormonal induction (5 μg/kg LHRH-A3, 600 IU/kg hCG and 2 mg/kg DOM) and artificial insemination, and the tyrb (tyrosinase b) or csf1ra (colony-stimulating factor 1 receptor a) gRNA and Cas9 mRNA were microinjected into the fertilized eggs at the one-cell stage for targeted gene editing. The target site was designed on the first exon of tyrb and the second exon of csf1ra, respectively. The efficiency of mutation was gRNA and Cas9 mRNA concentration dependent, and 400 ng/μl gRNA and 800 ng/μl Cas9 mRNA were recommended as the appropriate injection dose for genome editing in LMB. Enzyme-digestion and sanger-sequencing demonstrated that the CRISPR/Cas9 system is available for the gene editing of LMB. The tyrb mutation resulted in reduced melanin and even albinism in eye and body of larvae, while the csf1ra mutation led to reddish body color, reduced xanthophores and melanophores in juvenile and adult fish with high mutation rate. Our results indicated that the CRISPR/Cas9 gene-editing system was successfully established in LMB. The mutation of body color related genes provided great convenience for the observation of mutant phonotypes and produced improved strains of LMB. It is the first successful application of gene-editing technology in LMB, which has taken a key step in studying the gene function and molecular mechanism and provided a novel method for improving the economic traits of LMB aquaculture.